Evaluation of High-Throughput SARS-CoV-2 Serological Assays in a Longitudinal Cohort of Patients with Mild COVID-19: Clinical Sensitivity, Specificity, and Association with Virus Neutralization Test. (5th January 2021) - Bal, Antonin; Pozzetto, Bruno; Trabaud, Mary-Anne; Escuret, Vanessa; Rabilloud, Muriel; Langlois-Jacques, Carole; Paul, Adèle; Guibert, Nicolas; D'Aubarède-Frieh, Constance; Massardier-Pilonchery, Amélie; Fabien, Nicole; Goncalves, David; et al.
Abstract: Background: The association between SARS-CoV-2 commercial serological assays and virus neutralization test (VNT) has been poorly explored in mild patients with COVID-19. Methods: 439 serum specimens were longitudinally collected from 76 healthcare workers with RT-PCR-confirmed COVID-19. The clinical sensitivity (determined weekly) of 9 commercial serological assays were evaluated. Clinical specificity was assessed using 69 pre-pandemic sera. Correlation, agreement, and concordance with the VNT were also assessed on a subset of 170 samples. Area under the ROC curve (AUC) was estimated at 2 neutralizing antibody titers. Results: The Wantai Total Ab assay targeting the receptor binding domain (RBD) within the S protein presented the best sensitivity at different times during the course of disease. The clinical specificity was greater than 95% for all tests except for the Euroimmun IgA assay. The overall agreement with the presence of neutralizing antibodies ranged from 62.2% (95%CI; 56.0–68.1) for bioMérieux IgM to 91.2% (87.0–94.2) for Siemens. The lowest negative percent agreement (NPA) was found with the Wantai Total Ab assay (NPA 33% (21.1–48.3)). The NPA for other total Ab or IgG assays targeting the S or the RBD was 80.7% (66.7–89.7), 90.3% (78.1–96.1), and 96.8% (86.8–99.3) for Siemens, bioMérieux IgG, and DiaSorin, respectively. None of the commercial assays have sufficient performance to detect a neutralizing titer of 80 (AUC < 0.76). Conclusions: Although some assays show a better agreement with VNT than others, the present findings emphasize that commercialized serological tests, including those targeting the RBD, cannot substitute a VNT for the assessment of functional antibody response.